2000
DOI: 10.1523/jneurosci.20-14-05200.2000
|View full text |Cite
|
Sign up to set email alerts
|

Increased Binding Activity at an Antioxidant-Responsive Element in the Metallothionein-1 Promoter and Rapid Induction of Metallothionein-1 and -2 in Response to Cerebral Ischemia and Reperfusion

Abstract: Metallothioneins (MTs) are cysteine-rich metal-binding proteins that are potentially involved in zinc homeostasis and free radical scavenging. The expression pattern of MT-1 and the binding activity of various MT-1 promoter elements were investigated after mild focal cerebral ischemia in the rat. Transient focal ischemia was induced by occluding both common carotid arteries and the right middle cerebral artery for 30 min. By the use of real-time quantitative PCR, a 10-fold increase in MT-1 and -2 mRNA levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 46 publications
1
44
1
Order By: Relevance
“…EpREs have been found in the promoter regions of various genes, e.g. those encoding glutathione S-transferase, NADPH: quinone oxidoreductase, the heavy and light subunits of ␥-GCS, ferritin L subunit, metallothionein-1, and thioredoxin (9,10,(22)(23)(24)(25). The common function of these proteins is for cell defense against xenobiotics and oxidants.…”
Section: Discussionmentioning
confidence: 99%
“…EpREs have been found in the promoter regions of various genes, e.g. those encoding glutathione S-transferase, NADPH: quinone oxidoreductase, the heavy and light subunits of ␥-GCS, ferritin L subunit, metallothionein-1, and thioredoxin (9,10,(22)(23)(24)(25). The common function of these proteins is for cell defense against xenobiotics and oxidants.…”
Section: Discussionmentioning
confidence: 99%
“…MT transcripts are most significantly upregulated in cells neighboring sites following ischemic damage with increased expression lasting for extended periods following trauma. 41 MT1 and hemeoxygenase 1 (HO-1) genes, which were also significantly upregulated, have been shown to be increased following hypoxic preconditioning. 42 Thus, taken together, there is evidence not only for oxidative stress responses within the schizophrenia prefrontal cortex but also support that this stress may be partially or specifically due to hypoxic conditions.…”
Section: 41mentioning
confidence: 99%
“…؊/؊ mouse brain Induction of Nrf2-dependent gene expression normally occurs in the ischemic penumbra after stroke, raising the possibility that Nrf2 activation may be an endogenous response to limit stroke damage (van Lookeren Campagne et al, 1999;Campagne et al, 2000;Laxton et al, 2001;Liverman et al, 2004). Notably, data from gel-shift assays indicated that binding to the ARE sequence found in Nrf2 target genes such as metallothionein-1 and metallothionein-2 was upregulated after transient forebrain ischemia in rat (Campagne et al, 2000).…”
Section: Basal and Inducible Phase 2 Enzyme Activities Are Suppressedmentioning
confidence: 99%